Inheriting the world : the atlas of children's health and the environment - Gordon, Bruce (Bruce Allan) (World Health Organization, 2004)
Every child has the right to live in a healthy, supportive environment - an environment that encourages growth and development, and protects from disease. Many of the world s children, however, are exposed to hazards in the very places that should be safest - the home, school and community. Considering that their growing bodies are particularly sensitive to environmental threats, the final burden of childhood disease is substantial. Every year, more than three million children die due to unhealthy environments. This atlas articulates where and why more than three million children die every year due to unhealthy environments. It tackles issues as diverse as the devastating and largely unknown impact of indoor air pollution, the unfashionable tragedy of sanitation, and complex emerging issues like climate change. Full-colour maps and graphics clearly demonstrate the threats that children face everywhere, and underscore the impact of poverty on children s health. While this crisis cannot be ignored and demands urgent action, success stories, such as the Montreal Protocol, show a way forward for the world to make sure that our children will inherit a safer planet and a brighter future.